Application of FLP-FRT System to Construct Unmarked Deletion in Helicobacter pylori and Functional Study of Gene hp0788 in Pathogenesis - Ji, Xiaofei; Wang, Ying; Li, Jiaojiao; Rong, Qianyu; Chen, Xingxing; Zhang, Ying; Liu, Xiaoning; Li, Boqing; Zhao, Huilin (Frontiers in microbiology, 2017)
is a Gram-negative, microaerophilic bacterium associated with human gastric diseases. Further investigations on virulence genes are still required to clarify the pathogenic mechanism of and the heterogeneous problem of infection. In order to develop an efficient and accurate method to study gene functions in pathogenesis, an unmarked deletion method for both a single gene and a large fragment was established based on the FLP-FRT recombination system. Using this method, the gene , encoding an outer membrane protein (HofF), was deleted. Deletion of did not affect growth or motility of , but reduced the adherence of the bacteria to gastric epithelial cells. The apoptosis of GES-1 cells caused by infection was also reduced by the defection of . These suggest that takes part in the bacterium-host interaction and plays an important role in infection. Furthermore, a large genomic fragment deletion from to in pathogenicity island was also successfully achieved using FLP-FRT method. The innovative application of the FLP-FRT recombination system in to construct unmarked deletion would provide a helpful tool for further function research of putative pathogenic genes and contribute to the understanding of pathogenesis.